ANALISIS DETERMINAN HARGA PROPERTI RESIDENSIAL DI INDONESIA - Rahmawati, Okky; SE, Sasongko (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The main purpose of this study is to analyze the determinants of housing prices in Indonesia. This study examines the dynamic causal relationships between house prices and their six determinants, such as- demand for housing loans, interest rates (BI rate), GDP, inflation, prices of building materials (IHPB construction), and wages. Used model vector error correction (VECM), the variance decomposition concluded that the price of materials mainly explains the variability in housing prices. In the short term the determinants has no effect, while in the long term the determinants could influence the movement of housing prices which is reflected through the Residential Property price index (IHPR). Keywords: Residential Property Prices Index, Mortgages Credit, BI rate, Gross Domestic Bruto, Inflation, Construction Index,Wages, VECM